The Career Indecision Profile: Measurement Equivalence in Two International Samples. (February 2014) - Carr, Andrea; Rossier, Jérôme; Rosselet, Julien G.; Massoudi, Koorosh; Bernaud, Jean-Luc; Ferrari, Lea; Nota, Laura; Soresi, Salvatore; Rowe-Johnson, Meaghan; Brown, Steven D.; Roche, Meghan
This study tested for the measurement equivalence of a four-factor measure of career indecision (Career Indecision Profile–65 [CIP-65]) between a U.S. sample and two international samples; one composed of French-speaking young adults from France and Switzerland and the other of Italian adolescents. Previous research had supported the four-factor structure of the CIP-65 in both the United States and Iceland but also showed that items on two of the four scales may be interpreted differently by young adults growing up in these two countries. This study extends previous research by testing whether the four CIP-65 factors are measured equivalently in two additional international samples. Results largely supported the configural and metric invariance of the CIP-65 in the United States and international samples, but several scales showed a lack of scalar invariance. Some explanations are offered for these findings along with suggestions for future research and implications for practice.